A putative pyruvate transporter TaBASS2 positively regulates salinity tolerance in wheat via modulation of ABI4 expression. Issue 1 (December 2016) - Zhao, Yang; Ai, Xinghui; Wang, Mengcheng; Xiao, Langtao; Xia, Guangmin
Abstract Background High salinity adversely affects crop production. Pyruvic acid is the precursor of abscisic acid (ABA) and other chemicals that are synthesized in chloroplast, some of which are involved in the response to salt. The transportation of pyruvic acid into chloroplast is mediated by pyruvate transporters. However, whether pyruvate transporters are involved in salt response has not been studied so far. Here, we answered this issue by assessing the function of a wheat pyruvate transporter in salt response. Results A pyruvate transporterTaBASS2 was isolated from salt-tolerant wheat cultivar Shanrong 3. The expression ofTaBASS2 was induced by NaCl stress as well as H2 O2 and ABA treatments. Constitutive expression ofTaBASS2 inArabidopsis bass2-1 mutant complemented the mevastatin-sensitive phenotype that reflects the deficiency of transporting pyruvic acid into chloroplast. Overexpression ofTaBASS2 enhanced salinity tolerance and reactive oxygen species scavenging in wheat.Arabidopsis constitutively expressingTaBASS2 also exhibited enhanced tolerance to salinity and oxidative stress. InArabidopsis, TaBASS2 repressed the expression ofABA INSENSITIVE 4 (ABI4 ), a node linking ABA signaling and plastid retrograde signaling pathways. However, the enhanced salinity tolerance ofTaBASS2 overexpressionArabidopsis was abolished whenABI4 expression was restored to the level of wild-type through overexpressingABI4 . Conclusions Our work demonstrates thatTaBASS2 enhances salinity tolerance of plants via modulatingABI4 expression. This indicates that pyruvate transporters indeed participate in the interaction of plants with environmental stimuli.